Barriers and enablers to kangaroo mother care prior to stability from perspectives of Gambian health workers: A qualitative study - Cho, Ying Chun; Gai, Abdou; Diallo, Brahima A.; Samateh, Ahmadou Lamin; Lawn, Joy E.; Martinez-Alvarez, Melisa; Brotherton, Helen (Frontiers in Pediatrics, 2022)
Aims: Kangaroo mother care (KMC) is an evidence-based intervention recommended for stable newborns <2000g. Recent trials have investigated survival benefits of earlier initiation of KMC, including prior to stability, with WHO’s iKMC trial showing 25% relative risk reduction for mortality of neonates 1 – 1.8kg at tertiary Indian and African neonatal units (NNU). However, evidence is lacking about how to safely deliver this intervention to the most vulnerable neonates in resource limited settings (RLS). Our study aimed to understand barriers and enablers for early KMC prior to stability from perspectives of neonatal health care workers (HCW) in a high neonatal mortality RLS. Methods: This qualitative study was conducted at Edward Francis Small Teaching Hospital (EFSTH), the main neonatal referral unit in The Gambia. It was ancillary study to the eKMC clinical trial. Ten semi-structured interviews were conducted with all neonatal HCW cadres (4 nurses; 1 nurse attendant; 5 doctors; all Gambian). Study participants were purposively selected, and saturation was reached. Thematic analysis was conducted using Atun’s conceptual framework for evaluation of new health interventions with methods to ensure data reliability and trustworthiness. Results: HCW's perceptions of early KMC prior to stability included recognition of potential benefits as well as uncertainty about effectiveness and safety. Barriers included: unavailability of mothers during early neonatal unit admission; safety concerns with concomitant intravenous fluids and impact on infection prevention control; insufficient beds, space, WASH facilities and staffing; and lack of privacy and respectful care. Enablers included: education of HCW with knowledge transfer to KMC providers; paternal and community sensitization and peer-to-peer support. Conclusions: Addressing health systems limitations for delivery of KMC prior to stability is foundational with linkage to comprehensive HCW and KMC provider education about effectiveness, safe delivery and monitoring. Further context specific research into safe and respectful implementation is required from varied settings and should include perceptions of all stakeholders, especially if there is a shift in global policy towards KMC for all small vulnerable newborns.